Peran Perawat Terhadap Upaya Pencegahan Kematian Ibu di Puskesmas Rumaat Kabupaten Maluku Tenggara - haluruh, John Davison; Tanlain, Robeka; Kelabora, Jonathan; Batmomolin, Agnes (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The Maternal Mortality Rate (MMR) in Indonesia until 2018 is still high at around 305/100,000 KH. Likewise the MMR in Maluku Province is 52/100,000 KH. There are various factors that cause maternal death, one of which is education and counseling by health workers at first level health facilities (FKTP), especially by nurses as the front line in public health services that are not optimal. This study aims to identify the relationship between the role of nurses as educators and as counselors in efforts to prevent maternal mortality in the coastal community of the Rumaat Public Health Center, Southeast Maluku Regency using a cross-sectional approach. The sampling technique was total sampling, namely all nurses at the Rumaat Health Center, totaling 39 people. The results showed that the role of nurses as educators and counselors had a significant relationship with the prevention of maternal death in the coastal community of the Rumaat Health Center, Southeast Maluku Regency (p<0.05). This shows that nurses play a role in preventing maternal death at the Rumaat Health Center in Southeast Maluku Regency through their role as educators and counselors. To maintain and improve the welfare of pregnant women in the working area of ​​the Rumaat Health Center, nurses at the Rumaat Health Center in Southeast Maluku Regency must continue to provide education to pregnant women about the importance of nutritional intake, antenatal checks, rest and a healthy lifestyle to avoid danger during pregnancy followed by giving praise on the decision of pregnant women to carry out regular prenatal checks, listen to complaints, and provide support, as well as accompany mothers and families who have health problems to overcome their problems.